IMPROVEMENT OF SILKWORM (BOMBYX MORI L.) HYBRIDS FOR COCOON AND EGG PRODUCTION USING HONEY-ENRICHED MULBERRY (MORUS ALBA L.) LEAVES - C. M. Almojuela; G. E. Arellano; E. M. Barrameda2 and R. D. Supsup (Journal of Animal and Plant Sciences, 2022)
The study aimed to determine the performance of six (6) parental F1 silkworm hybrids fed with mulberry leaves enriched with honey concentrations. Evaluation of the different silkworm hybrids was based on cocoon and egg production parameters. Treatments were arranged in Split Plot in Randomized Complete Block Design (RCBD). Data were analyzed using Analysis of Variance (ANOVA) and comparison of treatment means were determined using Tukey’s Honest Significant Difference (HSD) Test. Interaction of honey concentration and silkworm hybrids was tested using Fisher’s protected Least Significant Difference (LSD). Mulberry leaves enriched with 30% honey concentration gave higher cocoon yield box-1 when fed to silkworm hybrids DMMMSU 201, DMMMSU 208, DMMMSU 210 and DMMMSU 215; and 45% honey concentration was best for DMMMSU 201. Hybrid DMMMSU 210 gave higher single cocoon shell weight and cocoon shell percentage with a 15% honey-enriched diet. Hybrids DMMMSU 210 gave higher hatching percentage with 15% and 30% honey enrichment while DMMMSU 201, 202 and 208 responded positively with all the treatment concentrations. The effect of honey-enriched mulberry on cocoon and egg parameters could be attributed to honey concentrations.
Keywords: Silkworm hybrids; Honey concentrations; Egg production; Cocoon quality; Mulberry leaves